Vegetation and pastoral dynamics in the southern Ethiopian rangelands: Implications for theory and management - Coppock, D. Layne (Overseas Development Institute, 1993)
This paper reviews research on aspects of vegetation change and pastoral population dynamics in the southern Ethiopian rangelands during the 1980s and relate these findings to the debate on equilibrial versus non-equilibrial patterns of pastoral ecosystem dynamics. Examines pastoral dynamics and perceptions of change, long-term effects in four lower semi-arid regions and effects in one lower semi-arid and two upper semi-arid regions. Also discusses migration of pastoralists in response to local resource base condition, the role of livestock grazing and corralling in relation to nutrient redistribution, and the role of woody encroachment in facilitating recovery of the herbaceous layer.